# Yahoo奇摩 網頁搜尋

廣告

1. 排列方式

1. ### Let A be a 3x3 matrix such that A^2 = O , where O is the 3x3 zero matrix. Prove that det(A + I) > 0, where I is the 3x3 identity matrix.?

... that det(A + I) > 0, where I is the 3×3 identity matrix. Solution： det(A + I) = det[(A/2 + I...

分類：科學及數學 > 數學 2018年09月28日

2. ### 數學代數二角比問題求解?

Sol Sin36°=Sin(90°－54°) Sin36°=Cos54° 2sin18°Cos18°=4Cos^3 18°－3Cos18° Cos18°<>0 2Sin18°=4Cos^2 18°－3 2Sin18°=4(1－Sin^2 18°)－3 2Sin18°=4...

分類：科學及數學 > 數學 2018年06月14日

3. ### 7C羅盤模型是指什麼?

...（企業內部的行銷傳播），時刻銘記企業識別系統（Corporate Identity）的理念、不要損毀名譽的同時去追求利益。（C-O-S）很重要...

分類：社會科學 > 經濟學 2017年08月15日

4. ### Prove the trigonometric identities. 2 cosθ sinθ / tan(90°- θ) ≡ 2sin²θ?

2 cosθ sinθ / tan(90°- θ) =2 cosθ sinθ / (1 / tanθ) =2 cosθ sinθ tanθ =2 cosθ sinθ × sinθ/cosθ =2sin²θ

分類：科學及數學 > 數學 2017年08月11日

5. ### Donald Trump was inaugurated as the 45th president of the United States on the steps in front of the Capitol Building in Washington.?

(1)stand on something called doorstep. (2)not lost on me=still positively influence me by Jewish. (3)more than enough information that you can use to ...

分類：社會及文化 > 語言 2017年01月21日

6. ### 急!想問有關positive and negative correlation的問題?

... your case, if a positive correlation exists between "local identity" and "assimilation attitude", then YES! Your assumption ...

分類：社會科學 > 心理學 2016年10月05日

7. ### I=(1001)matrix?

...that (I + S) is non-singular, where I is the 2×2 identity matrix. (a) Show that (I + S)(I - S) = (I...

分類：科學及數學 > 數學 2016年09月12日

8. ### A,B,C are constants , find A,B,C 1.If (x+2)(Cx+B)=3x^2+4x+A is an identity 2.If A(2x+1)^2-3Bx+(B-C)=(4x-1)(x-4) is an identity?

1. (x + 2)(Cx + B) ≡ 3x² + 4x + A Put x = -2. 0 = 3(4) + 4(-2) + A A = -4 Put x = 0. 2B = A = -4 B = -2 Compare coefficient of x². C = 3 2. A(2x + 1)² ...

分類：科學及數學 > 數學 2016年07月23日

9. ### trigo compulsory part?

... 0 ≤ 1 + 2k ≤ 2 -1 ≤ 2k ≤ 1 -1/2 ≤ k ≤ 1/2 Trigonometric Identity sin²θ + cos²θ = 1 ...

分類：科學及數學 > 數學 2016年06月16日

10. ### F2 Maths Factorization using identites 唔該!!!?

m^2-n^2+6m-2n+8 =m^2+6m+9-(n^2+2n+1) =(m+3)^2-(n+1)^2 =(m+3+n+1)(m+3-n-1) =(m+n+4)(m-n+2)

分類：科學及數學 > 數學 2015年10月17日